2020
DOI: 10.1186/s40249-020-00712-4
|View full text |Cite
|
Sign up to set email alerts
|

High multiple mutations of Plasmodium falciparum-resistant genotypes to sulphadoxine-pyrimethamine in Lagos, Nigeria

Abstract: Background: Plasmodium falciparum-resistance to sulphadoxine-pyrimethamine (SP) has been largely reported among pregnant women. However, the profile of resistance markers to SP dihydrofolate reductase (dhfr) and dihydropteroate synthase (dhps) in the general population are varied and not frequently monitored. Currently, SP is used as partner drug for artemisinin combination therapy (SP-artesunate) in some sub-Saharan African countries or as a prophylactic drug in intermittent preventive treatment of malaria du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 48 publications
12
27
0
Order By: Relevance
“…Interestingly, to date, the I431 V mutation has not been observed in other parts of Africa. In concordance with previous studies [ 42 , 49 ], this mutation was observed in combination with other Pfdhps mutations (S436 A /A437 G /A581 G /A613 S ), suggesting this mutation may have occurred only in the presence of the other Pfdhps mutations. The implications of this combination of Pfdhps mutations remain unclear.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, to date, the I431 V mutation has not been observed in other parts of Africa. In concordance with previous studies [ 42 , 49 ], this mutation was observed in combination with other Pfdhps mutations (S436 A /A437 G /A581 G /A613 S ), suggesting this mutation may have occurred only in the presence of the other Pfdhps mutations. The implications of this combination of Pfdhps mutations remain unclear.…”
Section: Discussionsupporting
confidence: 92%
“…Results from this study demonstrate that the prevalence of the Pfdhfr IRN triple mutant is very high, implying these mutants are well established in this region, similar to observations made previously in Benin and in many African countries [ 16 , 18 , 39 , 40 ]. In contrast, the prevalence of multiple mutations in the Pfdhps gene was low, with the majority of parasites having only a single mutation at codon A437 G and 29.3% of the parasites with a double mutant (S436 A /A437 G ), as commonly observed in West Africa [ 18 , 21 , 41 , 42 ]. Only a handful of isolates had mutations at codons K540 E (2.6%), A581 G (2.6%), and A613 S (4.6%).…”
Section: Discussionmentioning
confidence: 97%
“…Polymorphism data from our study showed high prevalence of mutant I 51 (88.9%) and N 108 (80.8%) dhfr alleles and mutant G 437 (82.3%) dhps allele. Similar prevalence of these mutant dhfr and dhps alleles have been recorded in Nigeria 11 , 13 and other West African countries 14 , 15 . Although prevalence of these mutant alleles are generally high in West Africa 16 , lower prevalence (26.5–56.25) have been recorded in other West African countries 4 , 17 .…”
Section: Discussionsupporting
confidence: 77%
“…Since the deployment of SP in Nigeria as IPTp in 2001 10 and SMC in 2013 11 , there have been various reports of these point mutations in both dhfr and dhps genes associated with SP resistance in various parts of the country 11 , 12 . Reports of high prevalence of the triple mutant genotype of dhfr (N 51 I, C 59 R and S 108 N) in addition to the A 437 G mutation in the dhps gene is common in Nigeria 13 . However, occurrence of the quintuple dhfr + dhps mutation comprising of N 51 I, C 59 R and S 108 N + A 437 G and K 540 E is scarce 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation